Evaluasi Pelaksanaan Kurikulum Pendidikan Agama Islam (PAI) di MA Almutohhirin: Sebuah Studi Evaluatif - Anik Nuzuliati (Muaddib: Jurnal Pendidikan Agama Islam, 2026)
This study evaluates the implementation of the Islamic Religious Education (PAI) curriculum at MA Al Muthohhirin Wuluhan Jember using the CIPP evaluation model (Context, Input, Process, Product). Islamic Religious Education plays an important role in developing students’ faith, moral character, and religious behavior; therefore, its curriculum implementation needs to be systematically reviewed to ensure alignment with the educational goals of the madrasah. This research applies a qualitative evaluative approach. The research subjects include the principal and Islamic Religious Education teachers, while students serve as supporting data sources. Data were collected through observation, interviews, questionnaires, and documentation. The data were analyzed descriptively using the four components of the CIPP model: context, input, process, and product. Data validity was ensured through source and technique triangulation. The findings are expected to provide a comprehensive description of the relevance of the curriculum context, the readiness of supporting resources, the quality of the learning process, and the outcomes and impacts on students. The results are expected to serve as an evaluative reference and a basis for recommendations to improve the quality of Islamic Religious Education curriculum implementation at MA Al Muthohhirin.